Law and Exception: The Structural Violence of Criminal Control - Amorim, Antônio Leonardo; Júnior, André Luiz de Resende (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This article starts from a critical view of modernity that aims to highlight the role of structural violence that constituted it in the Democratic State of Law. The aim is to highlight, based on a reading that starts from the political economy of punishment, the operationalization of modes of penal control in the center and on the margins of capital. Therefore, we use a dialectical methodology to highlight the insufficiencies of readings that understand modernity as an emancipatory phenomenon and to reveal the contradictions of the real movement of modern penal control, which is structured based on a violence that is structural and organized. From this, the aim is to understand how the processes of mediation between capital and criminal control institutions occur. Finally, we analyze how the law operates together with the exception of itself in order to constitute a permanent exception for the subordinate classes.